Answer:x=3
Step-by-step explanation:
D( x )
x+2 = 0
x = 0
x+2 = 0
x+2 = 0
x+2 = 0 // - 2
x = -2
x = 0
x = 0
x in (-oo:-2) U (-2:0) U (0:+oo)
(9*x-7)/(x+2)+15/x = 9 // - 9
(9*x-7)/(x+2)+15/x-9 = 0
(x*(9*x-7))/(x*(x+2))+(15*(x+2))/(x*(x+2))+(-9*x*(x+2))/(x*(x+2)) = 0
x*(9*x-7)+15*(x+2)-9*x*(x+2) = 0
9*x^2-9*x^2+8*x-18*x+30 = 0
30-10*x = 0
(30-10*x)/(x*(x+2)) = 0
(30-10*x)/(x*(x+2)) = 0 // * x*(x+2)
30-10*x = 0
30-10*x = 0 // - 30
-10*x = -30 // : -10
x = -30/(-10)
x = 3
x = 3
Answer:
(0,1) (0.333,0)
(7,0)
m=1
Step-by-step explanation:
I can simplify the formula with the data you gave me to do a simple formula like this: <span>4.25 k + 2 p = 12 I think this one explains in an easy way this. Hope it's good for you</span>
3.25 is the answer so copy down the answer its right